2000
DOI: 10.1007/s004199900072
|View full text |Cite
|
Sign up to set email alerts
|

On dimensionless numbers for dynamic plastic response of structural members

Abstract: A dimensional analysis is reported for the dynamic plastic response and failure of structural members, which includes material strain hardening, strain rate and temperature effects. Critical shear failure conditions are also discussed based on the dimensional analysis results. It is shown that the response number R n proposed in [3], is an important independent dimensionless number for the dynamic plastic bending and membrane response of structural members. However, additional dimensionless numbers are necessa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
48
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 70 publications
(48 citation statements)
references
References 24 publications
0
48
0
Order By: Relevance
“…[2,3,4,6,7], it has been demonstrated that the response number is an important dimensionless number extensively utilized for dynamic plastic response of structures made of rigid-perfectly plastic materials. Actually, it should be pointed out that Zhao's response number can be used to study the elastic, plastic and dynamic plastic problems, and this dimensionless number would have a more extensive utilization for structural dynamics.…”
Section: Including Those Expressions Presented Inmentioning
confidence: 99%
See 4 more Smart Citations
“…[2,3,4,6,7], it has been demonstrated that the response number is an important dimensionless number extensively utilized for dynamic plastic response of structures made of rigid-perfectly plastic materials. Actually, it should be pointed out that Zhao's response number can be used to study the elastic, plastic and dynamic plastic problems, and this dimensionless number would have a more extensive utilization for structural dynamics.…”
Section: Including Those Expressions Presented Inmentioning
confidence: 99%
“…A general dimensional analysis for structural mechanics has been discussed by Jones in [1], where important physical quantities in the dynamic inelastic response are considered in developing a complete set of dimensionless numbers using Buckingham Π theorem. The dimensionless numbers obtained from dimensional analysis are useful for scaling purpose and for organizing experimental model tests and numerical calculations to avoid any unnecessary repetition of the results in dimensionless space [2], Recently, a new dimensionless number, response number,…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations